GAMBARAN FUNGSI KOGNITIF MENGGUNAKAN EVENT RELATED POTENTIAL AUDITORIK PADA PENYANDANG DIABETES MELITUS TIPE 2 - Aryatama*, Bob Santoso Wibowo*, Suharko Soebardi**, Silvia F Lumempouw*,Joedo Prihartono*** (Neurona Majalah Kedokteran Neuro Sains, 2010)
INTRODUCTION ONE OF MANY COMPLICATIONS IN DIABETES MELLITUS DM THAT WAS STILL RARE TO BE DISCUSSED IS THE COGNITIVE DYSFUNCTION THE MOST FREQUENT NEUROPHYSIOLOGICAL STUDY BEING USED TO SCREEN COGNITIVE DYSFUNCTION WAS THE EVENTRELATED POTENTIAL ERP HOWEVER STUDIES ABOUT COGNITIVE DYSFUNCTION USING ERP IN TYPE2 DM WERE FEW